The Correlation Between Hypocalcemia and Clinical Level of Covid-19 Patients at Sebelas Maret University Hospital - Udroso, Anindya Cahyaningtyas Ardiyanti; Apriningsih, Hendrastutik; Raharjo, Ahmad Farih (Smart Medical Journal, 2023)
Introduction: Coronavirus Disease 2019 (Covid-19) can cause electrolyte imbalances, one of which is hypocalcemia. Hypocalcemia has been identified as a predictor of the severity of Covid-19. This research aimed to determine the correlation between hypocalcemia and the clinical degrees of Covid-19 patients at UNS Hospital.Method: This study used a cross-sectional design with a population of Covid-19 patients treated at the Covid-19 ward at UNS Hospital in 2020-2022. Samples were collected from medical records by purposive sampling technique that met the inclusion and exclusion criterias.Results: There were 90 cases of hypocalcemia in Covid-19 patients. Mild hypocalcemia (88.9%) was found more than severe hypocalcemia (11.1%). Hypocalcemia was more common in male sex (54.4%), aged 46-65 years (70%), and in moderate clinical degree (31.1%). The Kolmogorov-Smirnov statistical test results showed a significant correlation between hypocalcemia and the clinical degree of Covid-19 with p=0.009 (p<0.05). The Spearman statistical test results showed that there was a fairly strong and statistically significant correlation between hypocalcemia and the clinical degree of Covid-19 where r=0.310 and p=0.003 (p<0.05).Conclusion: There is a fairly strong and statistically significant unidirectional correlation between hypocalcemia and the clinical degree of Covid-19 patients.